Pemberdayaan Warga Kampung Tualang Melalui Pengolahan Tanaman Obat Keluarga Menjadi Jamu Seduh Instan - Hendrika, Yan; Kurnia Utama, Vonny; Bahri Riva’i, Syamsul; Yusmaharani; Masevani, Raisa (JDISTIRA - Jurnal Pengabdian Inovasi dan Teknologi Kepada Masyarakat, 2024)
This community service activity aims to empower housewives through the utilization of Family Medicinal Plants (TOGA) by transforming them into instant herbal drinks. The training focused on processing red ginger (Zingiber officinale var. rubrum) due to its extensive health benefits, such as anti-inflammatory, antioxidant, and analgesic properties. The activity involved 30 participants who received theoretical knowledge and hands-on practice on how to process red ginger into instant herbal drink products that are easy to prepare, hygienic, and have a longer shelf life. The results showed that participants were enthusiastic and actively engaged throughout the sessions. Evaluations before and after the training indicated a significant increase in knowledge. Previously, participants only grew medicinal plants as decoration without understanding their benefits and economic potential. The advantage of instant herbal drinks is their practicality in preparation, safety, and longer shelf life. Furthermore, this activity opened economic opportunities for participants through the development of small businesses based on instant herbal drinks. In conclusion, the training successfully enhanced the knowledge and skills of housewives in utilizing TOGA, particularly red ginger, and had a positive impact on economic empowerment. It is hoped that this program will continue with further assistance and development of other TOGA-based products.